Pemahaman Generasi Milenial Berinvestasi di Peer to Peer Lending - Ni Putu Mega Lestari (Universitas Pendidikan Nasional, 2019)
ABSTRACTThe development of digital technology, especially in the field of financial technology (fintech), always presents new innovations that invite the millennial generation's curiosity. Peer to peer lending is one form of fintech innovation in terms of investment which is becoming a trend in Indonesia. The purpose of this study was to determine the interest of the millennial generation of investing to be lenders in peer to peer lending. The writing method in this study is qualitative by conducting interviews (in-depth interviews) with millennial generation informants with birth ages from 1980 to 1990, or at the beginning of 2000. The results of this study are to measure the investment interest of millennial generations with understanding of the benefits and risks of peer to peer lending. From this research, it can be concluded that most millennials are hesitant and are not interested in becoming lenders in peer to peer lending. Millennials prefer to invest in other forms such as stocks, gold, deposits, savings, and property. Socialization and in-depth information about the benefits of investments in peer to peer lending is one of the things that needs to be done by the peer to peer lending platform providers. In addition, the role of government is also needed in regulating regulations to provide security and minimize the risk of default and fraud. The results of this study are expected to contribute to the provider of peer to peer lending platforms and can be a picture for millennial generations in making investment decisions in the digital era.